PARADIGMA PEMBELAJARAN HUMANISME PERSPEKTIF CARL R. ROGERS SERTA IMPLIKASINYA DALAM PEMBELAJARAN PAI - Moh. Afiful Khair; Atnawi Atnawi (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2022)
This study aims to explain the perspective of Carl R. Rogers, an initiator of the humanistic flow in learning Islamic Religious Education. In this study using the library research method or literature study. Research data obtained from the recording of books and journals. The object of study in this research is Carl R. Rogers' humanistic learning theory. The results of this study are in the form of a biography of a humanistic figure, Carl R. Rogers, understanding of Carl R. Rogers' perspective of humanism learning theory, the principles, weaknesses and strengths of humanism learning theory and its implications in learning Islamic Religious Education. The outline of this humanism learning theory is an educator, only as a facilitator whose job is to guide, ensure and supervise the learning process runs smoothly so that the transfer of knowledge runs optimally.